Efektivitas Pelaksanaan Program Pembangunan Infrastruktur di Desa Tahayadun Kecamatan Bokat Kabupaten Buol - Saprudin A. Saleh; Lucyane Djaafar; Roni Lukum (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The purpose of this study was to determine how effectively the village infrastructure development program was implemented in Tayadun Village, Bokat Sub-district, Buol District. This research uses a qualitative research type. The author used indicators of goal achievement, integration, and adaptation to assess indicators of development effectiveness. The research collected data through interviews, literature study, and observation. Data analysis was conducted by reducing data, presenting data, and making conclusions. The results showed that the effectiveness of the implementation of the Tayadun Village infrastructure development program was quite effective, went well although there were still obstacles faced by the village government, and was carried out on time.